Combined Electrostatic-Covalent Building of Au NPs Multilayers and Their Size-Enhanced Cohesive and SERS Properties. (14th February 2011) - Mougin, K.; Darwich, S.; Vidal, L.; Haidara, H.
Abstract : Multilayers of well-ordered and close-packed 2D nanostructures of gold nanoparticles (NPs) were fabricated using a layer-by-layer technique. Colloidal spherical Au NPs of 5 and 15 nm diameters were synthesized and, respectively, self-assembled in multilayers. The robustness of these systems was insured by a combination of electrostatic and covalent bonds between nanoparticles and linker molecules. The compacity of the superlattice was characterized by AFM observation and ellipsometry measurements. Evidence of stronger cohesion of multilayers of smaller NPs size was brought by submitting the systems to sonication test. The multilayers have also proved analytical potential when used to detect low concentration methylene blue molecules adsorbed on the Au nanoparticles, by surface-enhanced Raman spectroscopy (SERS). The detection sensitivity of these two sized Au NPs architectures was directly compared to an evaporated "bulk" Au thin film of equivalent thickness. Results have displayed a strong increase of the electromagnetic field enhancement with a decrease of the NPs size, whereas the bulk thin Au film was shown to be inefficient as a SERS substrate. These results bring a nice evidence of size effects on the global performance (SERS, cohesion) and hopefully on the stability of NPs based nanostructures.